The effect of work function difference between cathode and anode materials on the potential window of the supercapacitor. (1st February 2020) - Peng, Li; Wei, Xijun; Song, Kena; Peng, Huarong; Li, Li; Hu, Jingrui; Yang, Yibin; Zhang, Hongmei; Xiao, Peng
Abstract: The work function difference (WFD) between the two electrode materials has a positive effect on the potential window for the asymmetric supercapacitors (ASCs) theoretically, but there is no relevant investigation. Here, we use the kelvin probe force microscope to detect contact potential difference (CPD) which can well represent the WFD between carbon@K0·5 Mn2 O4 positive material and four metal oxides anode materials, namely MoO3, V2 O5, Fe2 O3 and WO3 respectively. What's more, the relationship between WFD and the potential window is studied by combining contact potential difference with electrochemical testing. We find that the as-fabricated carbon@K0·5 Mn2 O4 //MoO3 device exhibits the widest potential window of 2.42 V with the maximum WFD. As a result, the carbon@K0·5 Mn2 O4 //MoO3 have a high energy density of 66.7 Wh kg −1 at the power density of 5.95 kW kg −1 . Our study provides a new experimental reference for constructing supercapacitor devices with wide potential window and high energy density. Highlights: Reveal the effect of work function difference on the supercapacitors potential window. Assembled Carbon@K0·5 Mn2 O4 //MoO3 device exhibits voltage window of 2.42 V. The device shows energy density of 66.7 Wh kg −1 at the power density of 5.95 kW kg −1 .